2019
DOI: 10.1177/0143624418821079
|View full text |Cite
|
Sign up to set email alerts
|

Drainage and sewage system performance – Consequences of reductions in toilet flush volume

Abstract: This study aims to evaluate impacts of reducing toilet flush volume from 6.8 to 4.8 Lpf with laboratory and field studies. In laboratory, 260 tests were performed including water consumption, waste removal and solid transport tests, in 20 different toilets produced by national and international manufacturers. These tests demonstrated that a simple reduction in flush tank water level was not a viable solution for reducing flush volume, due to flush energy loss. Toilets are designed to work with certain water vo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 6 publications
0
1
0
Order By: Relevance
“…BW segregation, combined with the use of ultra-low-flush toilets, may induce the deposition of solids and the clogging of sub-horizontal domestic pipes and sewers designed under conventional paradigms, since approximately one-third of household water usage originates from toilet flushing. Furthermore, low-flush toilets could actually increase water consumption and BW dilution due to inefficient flushing and its repetition [36]. Segregated BW could be more efficiently collected by systems that are less infrastructure-and energy-intensive, such as vacuum sewers, as these only require about 0.5 L/flush [37] and would provide more concentrated WWTP influents, suitable for anaerobic treatment.…”
Section: Centralized Vs Decentralized Used-water Generation and Manag...mentioning
confidence: 99%
“…BW segregation, combined with the use of ultra-low-flush toilets, may induce the deposition of solids and the clogging of sub-horizontal domestic pipes and sewers designed under conventional paradigms, since approximately one-third of household water usage originates from toilet flushing. Furthermore, low-flush toilets could actually increase water consumption and BW dilution due to inefficient flushing and its repetition [36]. Segregated BW could be more efficiently collected by systems that are less infrastructure-and energy-intensive, such as vacuum sewers, as these only require about 0.5 L/flush [37] and would provide more concentrated WWTP influents, suitable for anaerobic treatment.…”
Section: Centralized Vs Decentralized Used-water Generation and Manag...mentioning
confidence: 99%
“…A study monitored the replacement of a WC of 6.8 L by a 4.8 L per flush and reported that the water consumption did not decrease due need of successive WC flushes (Valencio and Gonçalves, 2019). The authors also reported that the reduced flow might originate solid deposition in the initial sections of the sewage system.…”
Section: Networkmentioning
confidence: 99%